The MAX phase borides Zr2SB and Hf2SB - Rackl, Tobias; Johrendt, Dirk (Solid state sciences, 2020)
Zr2SB and Hf2SB were synthesized via solid-state reactions and the crystal structures were determined by powder X-ray diffraction. Both compounds crystallize in the hexagonal Cr2AlC-type structure (P63/mmc; Z = 2; Zr2SB a = 3.5001(1) Å, c = 12.2712(2) Å; Hf2SB a = 3.4671(1) Å, c = 12.1046(2) Å). The lattice parameters and bond lengths are slightly longer and the M6X octahedra are less distorted compared to the known carbides. Resistivity and magnetic measurements reveal that Zr2SB and Hf2SB are good metallic conductors and Pauli paramagnets. Ab-initio DFT calculations of the electronic structure confirm the nonmagnetic metallic state and show mainly ionic bonds, which are weaker than in the carbides. The elastic constants indicate that Zr2SB and Hf2SB are brittle and exhibit a less two-dimensional character compared to other MAX phases. [Display omitted] •The new MAX phase borides Zr2SB and Hf2SB have been discovered and characterized.•DFT calculations confirm the nonmagnetic metallic state and reveal mainly ionic bonds.•The bulk moduli are slightly smaller than in the carbides due to weaker Zr,Hf–B bonding.